2021
DOI: 10.3390/v13102086
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of H5 Highly Pathogenic Avian Influenza Viruses (Clade 2.3.4.4B) Circulating in Bulgaria in 2019–2021

Abstract: The first detection of a Highly Pathogenic Avian Influenza (HPAI) H5N8 virus in Bulgaria dates back to December 2016. Since then, many outbreaks caused by HPAI H5 viruses from clade 2.3.4.4B have been reported in both domestic and wild birds in different regions of the country. In this study, we characterized the complete genome of sixteen H5 viruses collected in Bulgaria between 2019 and 2021. Phylogenetic analyses revealed a persistent circulation of the H5N8 strain for four consecutive years (December 2016–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In the meantime, novel reassortants bearing the H5N8 HA and NA from other influenza viruses have been detected in nature. H5N1 viruses were detected in wild birds and domestic poultry in Russia and many countries in Europe, Africa, Asia, and North America [ 35–37 ]; H5N2 viruses were detected in wild birds in Serbia and domestic poultry in Taibei, China and Bulgaria [ 37 , 38 ]; H5N3 viruses were detected in wild birds in Denmark, France, Germany, Ireland, and Netherlands [ 37 ]; H5N4 were detected in wild birds in Germany, Netherlands, and Sweden [ 37 ]; and H5N5 viruses were detected in wild birds and domestic poultry in Iran and many countries in Europe [ 37 , 39 , 40 ]. In this study, we found that H5N8 wild bird viruses have encountered complex reassortment with local H5N6, H3N2, H4N6, and H6N6 domestic duck viruses, and with wild bird H9N2 virus, thereby producing multiple genotypes of H5N6 viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, novel reassortants bearing the H5N8 HA and NA from other influenza viruses have been detected in nature. H5N1 viruses were detected in wild birds and domestic poultry in Russia and many countries in Europe, Africa, Asia, and North America [ 35–37 ]; H5N2 viruses were detected in wild birds in Serbia and domestic poultry in Taibei, China and Bulgaria [ 37 , 38 ]; H5N3 viruses were detected in wild birds in Denmark, France, Germany, Ireland, and Netherlands [ 37 ]; H5N4 were detected in wild birds in Germany, Netherlands, and Sweden [ 37 ]; and H5N5 viruses were detected in wild birds and domestic poultry in Iran and many countries in Europe [ 37 , 39 , 40 ]. In this study, we found that H5N8 wild bird viruses have encountered complex reassortment with local H5N6, H3N2, H4N6, and H6N6 domestic duck viruses, and with wild bird H9N2 virus, thereby producing multiple genotypes of H5N6 viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses were initially classified into four groups including Group A, B, C, and D [ 4 , 10 ] but recent evaluations have seen this clade getting re-divided by the World Health Organization into eight further subclades (2.3.4.4a–h) [ 11 ]. Global surveillance data suggests that there are two dominant H5 HPAI clades 2.3.4.4b and 2.3.4.4h, in circulation across Asia, Europe and the Middle East [ 7 , 12–19 ], with seven human cases of H5N8 and five human cases of H5N6/2.3.4.4b reported in the Russian Federation and China, respectively, in 2021 [ 20 ]. Clade 2.3.4.4h viruses were also detected in wild migratory birds and humans in China, Vietnam, Mongolia and Bangladesh [ 11 , 15 , 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The last wild bird case for clade 2.2 and derivatives in Europe was detected in Germany in January 2009 6 . Another European incursion of a clade 2.3.2.1 virus occurred in 2009 but was not detected further west than Romania and Bulgaria, after being detected in Qinghai in China and Tyva in Russia 7 . In 2014/2015 a new intercontinental outbreak of HPAI H5 virus occurred, and since then HPAI H5 viruses have repeatedly caused large outbreaks in wild birds and poultry in Europe 5 , 6 .…”
Section: Introductionmentioning
confidence: 98%
“…After the breeding season many species become fully pelagic and can roam large parts of the northern Atlantic. The mid-Atlantic ridge outside Newfoundland is an important non-breeding area for seabirds, and is frequented by auks from Iceland (7), Svalbard (8) and Norway (9), including large numbers of Atlantic puffins and Brünnich guillemots, and by black-legged kittiwakes and northern fulmars originating from Iceland, Norway and the United Kingdom (7)(8)10). There these birds are joined by seabirds from Canadian and Greenlandic waters (11).…”
mentioning
confidence: 99%